High-Grade Basal Cell Adenocarcinoma Arising from the Parotid Gland: A Case Report and Review of the Literature - Çağatay Han Ülkü; Pembe Oltulu; Mustafa Cihat Avunduk (Turkish Archives of Otorhinolaryngology, 2017)

(untitled)
Basal cell adenocarcinomas are exceptionally rare and were first included in the histopathological classification of salivary gland tumors by the World Health Organization in 1991. These tumors are generally described as a low-grade malignancy with rare regional or distant metastasis. However, 48 basal cell adenocarcinoma cases arising from the major salivary glands have been described as high-grade malignancy in the English literature. Surgical excision and possible postoperative radiotherapy is the treatment of choice. Close follow up is mandatory for early detection of possible local recurrence. A 66-year-old female with high-grade basal cell adenocarcinoma of the parotid gland was presented in this study. Total parotidectomy with protection of the facial nerve integrity and postoperative radiotherapy were performed. At the most recent follow-up examination, 24 months after the surgery, the patient had no complaints and there was no sign of disease recurrence.